Pengaruh Kemampuan Literasi Matematis Terhadap Kemampuan Pemecahan Masalah Materi SPLDV Siswa SMP - Rosidah; Sopiany, Hanifah Nurus (Papanda, 2025)
This study aims to identify the effect of mathematical literacy skills on the problem solving skills of grade IX students. The method used was ex post facto research with a quantitative approach. The study population included all ninth grade students at SMPN 1 Telagasari. The sampling used simple random sampling technique to obtain a sample of 38 students from class IX H. The research was conducted in one meeting, where the research instruments in the form of mathematical literacy tests and problem solving tests were distributed to all students in the sample class. The data collection technique was carried out through giving written tests which were arranged based on the ability indicators of each variable. Data analysis using covariance analysis technique showed that mathematical literacy ability has an influence of 19.4% on students problem solving ability. This finding shows the importance of mathematical literacy in supporting students problem solving skills.